Cohort profile: the potentially preventable burden of community-acquired pneumonia in South African adults in the era of widespread PCV13 immunisation and antiretroviral therapy roll-out, before and during the COVID-19 pandemic – the multicentre, multimethod PotPrev Study - Jo Southern; Kennedy Otwombe; Eileen Dunne; Khuthadzo Hlongwane; Bradford D Gessner; Michelle Wong; Cheryl Cohen; Anne von Gottberg; Elizabeth Begier; Sharon Gray; Ebrahim Variava; Tumelo Moloantoa; et al. (BMJ Open)
Purpose In the setting of an established childhood pneumococcal vaccination programme with immediate initiation and treatment of antiretroviral therapy (ART) for people living with HIV (PLWH), the risk of adult pneumococcal community-acquired pneumonia (CAP) is not recently described. We aimed to investigate CAP incidence, recurrence, mortality, risk factors and microbiology before and during the COVID-19 pandemic.Participants Adults aged ≥18 years were enrolled in three South African provinces from March 2019 to October 2021, with a brief halt during the initial COVID-19 lockdown. The first group, PdCAP, a surveillance cohort, had their data abstracted to estimate the population incidence of physician-diagnosed CAP by counting incident CAP patients presenting to emergency rooms (ER) and mapping them to catchment areas linked to census data. From those admitted to wards from ERs, a prospective cohort (HospCAP) was enrolled and followed up to 1 year after discharge. Microbiology testing was performed and data were abstracted and collected for economic assessments. A third group (StART) of PLWH without respiratory illness at enrolment, attending primary healthcare clinics to initiate or reinitiate ART, was prospectively enrolled and followed. HospCAP and StART participants (totalling 2950 participants) were followed for at least 1 year and assessed for CAP episodes, hospitalisations and mortality.Findings to date Surveillance identified 6546 patients attending ERs with physician-diagnosed CAP; 61/6546 (0.9%) died in the ER. We prospectively enrolled 2000 hospitalised patients with CAP of whom 1079/2000 (54.0%) were PLWH. Overall, 271/2000 (13.6%) hospitalised CAP patients died during their first admission and 298/2000 (14.9%) died during follow-up. Among StART cohort, 18/950 (1.9%) died during follow-up.Future plans Planned analyses include incidence estimates of pneumococcal serotype-specific adult CAP and its recurrence, using Urinary Antigen Detection assay results to model the burden of pneumococcal CAP better and health economics analyses.